The role of metaphor in the Israeli-Palestinian conflict a cognitive linguistic approach - Ahmad Abdel Tawwab Sharaf Eldin; Wafya Hamouda; Walid Reda Ali; Hoda Soliman Mohamed (Cogent Arts & Humanities)
Metaphors have long been recognized as powerful tools that shape our understanding of the world. In the context of the Israeli-Palestinian conflict, metaphors play a crucial role in shaping perceptions and attitudes towards the conflict. This research explores the connection between Lakoff and Johnson's Conceptual Metaphor Theory and the role of metaphor in the Israeli-Palestinian conflict from a cognitive linguistic perspective. The study focuses on the use of metaphorical language by Israeli Prime Minister Benjamin Netanyahu and Palestinian Authority President Mahmoud Abbas during the period of April 2023 to September 2023. Applying Lakoff and Johnson's approach, the research aims to uncover the specific metaphors employed by these leaders to frame the conflict in a manner that serves their respective interests and narratives. The research objective is to gain a more nuanced understanding of how metaphors shape the discourse surrounding the Israeli-Palestinian conflict. By exploring the cognitive and linguistic strategies used by political actors, the study seeks to elucidate the underlying mechanisms through which metaphors can be leveraged to construct, perpetuate, and potentially transform the conflict narrative. The findings of this research are expected to offer valuable insights into the role of language in shaping perceptions, identity formation, and the justification of political actions within the context of the Israeli-Palestinian conflict. The analysis of metaphorical patterns used by the key stakeholders will illuminate how cognitive frames are established, maintained, and potentially challenged, ultimately contributing to a more comprehensive understanding of the conflict's dynamics.